Determination of Growth Performance of Lambs and Fertility Characteristics of Karayaka Sheep Raised in Amasya - Caner Tamer; Emre Şirin (Turkish Journal of Agriculture: Food Science and Technology, 2021)
This study was carried out to determine the growth and reproductive performance of Karayaka sheep in Amasya province within the scope of National Animal Breeding Project. Data were collected from 17529 Karayaka lambs of 20120 Karayaka sheep which were born during 2012 to 2015 birth season. In this study, the live weights, survival rates of the lambs in various periods and reproductive traits of Karayaka ewes were investigated. In this study, the live weights, daily live weight gain, survival rates (90th day) and reproductive traits of Karayaka ewes were investigated. The averages of reproductive traits of Karayaka sheep such as infertility, fertility, twins, fecundity, litter size and survival rate were 13.8%, 86.2%, 7.20%, 0.867, 1.01 and 89.0% respectively. The effects of year, sex and type of birth on the birth weights and the live weights of 90 days (weaning) of Karayaka lambs were found to be significant. Daily live weight gain was affected only by year and sex.